2009
DOI: 10.1093/nar/gkp046
|View full text |Cite
|
Sign up to set email alerts
|

Targeting individual subunits of the FokI restriction endonuclease to specific DNA strands

Abstract: Many restriction endonucleases are dimers that act symmetrically at palindromic DNA sequences, with each active site cutting one strand. In contrast, FokI acts asymmetrically at a non-palindromic sequence, cutting ‘top’ and ‘bottom’ strands 9 and 13 nucleotides downstream of the site. FokI is a monomeric protein with one active site and a single monomer covers the entire recognition sequence. To cut both strands, the monomer at the site recruits a second monomer from solution, but it is not yet known which DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 60 publications
(131 reference statements)
2
48
0
Order By: Relevance
“…1A) necessary for dimerization and subsequent DNA cleavage (Bitinaite et al 1998). Specifically, we focused on amino acids D450 and D467, both previously shown to result in catalytically inactive FokI variants when mutated (Waugh and Sauer 1993;Sanders et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…1A) necessary for dimerization and subsequent DNA cleavage (Bitinaite et al 1998). Specifically, we focused on amino acids D450 and D467, both previously shown to result in catalytically inactive FokI variants when mutated (Waugh and Sauer 1993;Sanders et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that DNA-nicking enzymes allow homology-directed gene targeting in mammalian cells (Lee et al 2004;van Nierop et al 2009) and that nickases can be created by engineering naturally occurring restriction enzymes (Sanders et al 2009) or meganucleases (McConnell Smith et al 2009). However, these enzymes are not readily reprogrammed to target any predetermined DNA sequence and thus cannot be used to modify DNA sequences at user-defined genomic sites.…”
Section: Discussionmentioning
confidence: 99%
“…(Hereinafter, L and R refer to zinc finger proteins that bind to the left half-site and the right half-site, respectively, and EL and KK refer to two forms of obligatory heterodimeric FokI domains.) We introduced a mutation (Asp450 to Ala) at the active site of the FokI domain in one subunit to make a catalytically inert monomer (Sanders et al 2009), which can be paired with a wild-type monomer to yield a nickase. A wild-type monomer alone cannot induce a SSB because two FokI nuclease domains must dimerize to cleave a phosphodiester bond.…”
Section: Redesign Of a Zfn Pair To Make Nickasesmentioning
confidence: 99%
“…1F). A targeted single-strand break (SSB) has the potential to restrict repair to the homology-directed repair (HDR) pathway (28,29). Zinc-finger nickases (ZFNs) are well established for generating SSBs; more recently, this strategy even has been reported in TALENs (5,(29)(30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc-finger nickases (ZFNs) are well established for generating SSBs; more recently, this strategy even has been reported in TALENs (5,(29)(30)(31)(32). Therefore, a mutation at the active site (D450A) that abolishes catalytic activity without affecting protein dimerization or DNA recognition was introduced to FokI of the right hand of TALENs (28).…”
Section: Resultsmentioning
confidence: 99%